Jesus' resurrection fact or figment? : a debate between William Lane Craig and Gerd Ludemann - Craig, William Lane; Ludermann, Gerd; Tacelli, Ronald Keith, 1947-; Copan, Paul, 1962- (Downers Grove, IL IVP, 2000)
Includes bibliographical references.
Keywords: Jesus Christ -- resurrection